Effect of tool rotation in near-dry EDM process on machining characteristics of HSS. Issue 7 (19th May 2019) - Yadav, Vineet Kumar; Kumar, Pradeep; Dvivedi, Akshay
ABSTRACT: Rotary tool near-dry electrical discharge machining (RT-ND-EDM) is a process variant of EDM, which utilizes two phase dielectric medium instead of a conventional liquid or gaseous dielectric medium. The present work, RT-ND-EDM was investigated while machining of high speed steel (AISI M2 grade) using glycerin-air dielectric medium. The effect of various input process parameters was investigated on material removal rate (MRR), surface roughness (SR), and hole overcut (HOC). The input parameters considered were tool rotation speed, current, pulse on time, liquid flow rate, and gas pressure. Experiments were designed and conducted using response surface methodology. Regression models were also developed. The results revealed that the tool rotation speed has a significant effect on MRR, SR, and HOC. FE-SEM micrographs showed that the machined surfaces obtained by RT-ND-EDM have relatively lower micro-cracks, debris accumulation and craters. Also, deep through holes were successfully drilled in 24 mm plate using RT-ND-EDM process.